Deep brain stimulation lead-contact heating during 3T MRI: single- versus dual-channel pulse generator configurations. (1st March 2014) - Nazzaro, Jules M.; Klemp, Joshua A.; Brooks, William M.; Cook-Wiens, Galen; Mayo, Matthew S.; Van Acker III, Gustaf M.; Lyons, Kelly E.; Cheney, Paul D.
<x xml:space="preserve">Abstract</x> Background: Magnetic resonance imaging (MRI) after deep brain stimulation (DBS) carries the risk of heating at the lead-contacts within the brain. Objective/Hypothesis: To compare the effect of single- and dual-channel DBS implantable pulse generator (IPG) configurations on brain lead-contact heating during 3T MRI. Methods: A phantom with bilateral brain leads and extensions connected to two single-channel IPGs or a dual-channel right or left IPG was utilized. Using a transmit/receive head coil, seven scan sequences were conducted yielding a range of head-specific absorption rates (SAR-H). Temperature changes (ΔT) at the bilateral 0 and 3 lead-contacts were recorded, and normalized temperatures (ΔT/SAR-H) and slopes defining the ΔT/SAR-H over the SAR-H range were compared. Results: Greater heating was strongly correlated with higher SAR-H in all configurations. For each scan sequence, the ΔT/SAR-H of single-channel left lead-contacts was significantly greater than the ΔT/SAR-H of either dual-channel configuration. The slope defining the relationship between ΔT and SAR-H for the single-channel left lead (1.68°C/SAR-H) was significantly greater (p < 0.0001) than the ΔT/SAR-H slope for the single-channel right lead (0.97°C/SAR-H), both of which were significantly greater (p < 0.0001) than the ΔT/SAR-H slopes of left or right leads (range 0.68 to 0.70°C/SAR-H) in the dual-channel configurations. There were no significant differences in ΔT/SAR-H slope values between the dual-channel configurations. Conclusion: DBS hardware configuration using bilateral single-channel versus unilateral dual-channel IPGs significantly affects DBS lead-contact heating during 3T MRI brain scanning.